Vaccine Storage Profile in Public Health Centers in Kupang City - Jefrin Sambara; Ni Nyoman Yuliani; Maria Lenggu; Yohana Ceme (JURNAL INFO KESEHATAN, 2018)
Vaccines are the main component in the implementation of immunization, to achieve the maximum goal of immunization, it is necessary to support the management and availability of vaccines in sufficient quantities, quality and on time. All vaccines are biological products that range from easily damaged funds that require special handling in its management, especially storage. Vaccine storage in health service units such as the Public Health Center must be considered carefully. This study aims to determine the profile of vaccine storage at the Oepoi Public Health Center and Kupang City Public Health Center, which were assessed from 2 assessment categories, namely the completeness of the category including the availability of storage temperature monitoring and vaccine condition categories. The type of research used in this study is descriptive research. How to collect data by direct observation and using observation sheets, then the data is processed and then narrated. From the results of this study it was found that the completeness of the facilities included the availability of monitoring of storage temperature and condition of the vaccine at the Oepoi Public Health Center and Kupang City Public Health Center were available or available except in the Oepoi Public Health Center there was no freeze tag or freeze watch and no generator. And the condition of the vaccine at the Kupang City Public Health Center and the Oepoi Public Health Center are all available or available. So the overall profile of vaccine storage at the Oepoi Public Health Center and Kupang City Public Health Center is well available